Peningkatan Produktivitas UMKM Kopi Muria melalui Pelatihan Pengolahan Kopi - Khusna Dwijayanti; Noor Azizah; Mahmudatus Sa'diyyah (IKIP PGRI Bojonegoro, 2020)
ABSTRACTToday's muria coffee has a universal appeal to many people from different walks of life. Coffee lovers in Indonesia and abroad are also increasing. This triggered to develop the production of coffee muria as a regional superior product that should be lifted nationally. The problems faced by the perpetrators of SMEs coffee martia is the post-harvest processing of coffee, from the stage of sorting coffee, roasting, grinding, packaging, until the technique of coffee marketing. The purpose of this activity is to advance the muria coffee SMEs by educating SME players through coffee processing training and improving the coffee production process from manual to automatic using machines. The target of this activity was the coffee SMEs in Colo village, Dawe district. The method is done by giving machines and training on coffee processing. The output of this community service activity is the increasing in productivity of muria coffee from 3 kg / day to 15 kg / day. In addition, through coffee processing training, the quality of coffee is increasing by the uniformity of roasted coffee been, by using a roasting machine. Therefore, this activity is expected to encourage muria coffee products as the regional superior products.Keywords: coffee, muria, productivity, umkm ABSTRAKSaat ini kopi muria memiliki daya tarik universal bagi banyak orang dari berbagai lapisan masyarakat. Penikmat kopi di Indonesia maupun mancanegara juga terus meningkat. Hal tersebut memicu untuk mengembangkan produksi kopi muria sebagai produk unggulan daerah yang patut di angkat secara nasional. Permasalahan yang dihadapi oleh pelaku UMKM kopi muria adalah pengolahan pasca panen kopi, mulai tahap penyortiran kopi, roasting, grinding, packaging, sampai pada teknik pemasaran kopi. Tujuan kegiatan ini adalah memajukan UMKM kopi muria dengan melakukan edukasi kepada pelaku UMKM melalui kegiatan pelatihan pengolahan kopi dan perbaikan proses produksi kopi dari manual menjadi otomatis menggunakan mesin. Sasaran kegiatan ini adalah para pelaku UMKM kopi di kelurahan Colo kecamatan Dawe. Metode kegiatan dilakukan dengan cara pemberian mesin dan pelatihan pengolahan kopi. Luaran dari kegiatan pengabdian kepada masyarakat ini adalah meningkatnya produktivitas UMKM kopi muria dari 3 kg/ hari menjadi 15 kg/hari. Selain itu melalui pelatihan pengolahan kopi, dihasilkan peningkatan kualitas kopi yaitu hasil kematangan biji kopi sangrai yang seragam, dengan penggunaan mesin penyangrai kopi. Oleh karena itu, kegiatan ini diharapkan dapat mendorong produk kopi muria sebagai produk unggulan daerah.Kata Kunci: kopi, muria, produktivitas, umkm